Continuum approaches in the mechanics of curved composites and associated problems for structural members - Akbarov, SD; Guz, AN (SPRINGER, 2002)
A review is made of studies on the mechanics of curved composites carried out using continuum approaches. The relevant theory, problem formulations, and solution methods are considered and some typical results on the influence of structural distortion on the mechanical behavior of composites are analyzed. Subjects for near-term studies are proposed.
Keywords: SMALL-SCALE DISTORSIONS; STRESS-DISTRIBUTION; FORCED VIBRATION; PLATE; STABILITY; STRIP; Mechanics